Synthesis of Silica Nanostructures and Optimization of their Size and Morphology by Use of Changing in Synthesis Conditions - A. Elsagh (E-Journal of Chemistry)
The aim of the present research was optimization of practical conditions of the sol-gel synthesis. In so doing, silica particles were synthesized using sol-gel method and their size and morphology were investigated by use of SEM and TEM images. The effect of changing molar ratio of reactive including acids and silica pre-matter on the particles' morphology and size was studied. Also, acid type and silica pre-matter used in reaction was examined and the result product of the reaction were investigated in the presence of several acids and two types of silica pre-matter. The reaction time was studied as a very important factor in products' digestion phase which plays a significant role in determining particles’ size and rate of cracking products. Finally, in optimized conditions 50-80 nm diameter nanostructures were synthesized. These products can be used as drug delivery systems.